PENGARUH SERVICE RECOVERY DAN RELATIONSHIP MARKETING TERHADAP KEPUASAN PELANGGAN EL-JHON CABANG PAGAR DEWA - M. Thio Saputra; Islamuddin Islamuddin ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2023)
This study aims 1) To determine the effect of service recovery on customer satisfaction El-John Pagar Dewa Branch. 2) To determine the effect of relationship marketing on customer satisfaction El-John Pagar Dewa Branch. 3) To determine the effect of service recovery and relationship marketing on customer satisfaction El-John Pagar Dewa Branch. This type of research is a quantitative approach. The method used in this research is descriptive method. The population in this study were all customers at El-Jhon Pagar Dewa Branch. the sample amounted to 120 customers at El-Jhon Pagar Dewa Branch. Based on the results of research on the Effect of Service Recovery and Relationship Marketing on Customer Satisfaction El-Jhon Pagar Dewa Branch, the following conclusions can be drawn: 1) There is a positive and significant effect of Service recovery (X1) on customer satisfaction (Y) El-Jhon Bengkulu City. that the higher the service recovery, the higher the customer satisfaction. 2) There is an effect of Relationship Marketing (X2) on customer satisfaction (Y) El-Jhon Bengkulu City. it means that the higher the marketing relationship, the more customer satisfaction will be. 3) There is an effect of service recovery and relationship marketing together affecting El-John's customer satisfaction in Bengkulu City with a Fsig value of 0.003 <0.05. .Keywords: Service Recovery, Relationship Marketing, Satisfaction,